Nano/Microstructured Silicon-Carbon Hybrid Composite Particles Fabricated with Corn Starch Biowaste as Anode Materials for Li-Ion Batteries - Kwon, Hyun Jung; Hwang, Jang-Yeon; Shin, Hyeon-Ji; Jeong, Min-Gi; Chung, Kyung Yoon; Sun, Yang-Kook; Jung, Hun-Gi (AMER CHEMICAL SOC, 2020)
Silicon has a great potential as an alternative to graphite which is currently used commercially as an anode material in lithium-ion batteries (LIBs) because of its exceptional capacity and reasonable working potential. Herein, a low-cost and scalable approach is proposed for the production of high-performance silicon carbon (Si-C) hybrid composite anodes for high-energy LIBs. The Si-C composite material is synthesized using a scalable microemulsion method by selecting silicon nanoparticles, using low-cost corn starch as a biomass precursor and finally conducting heat treatment under C3H6 gas. This produces a unique nano/microstructured Si-C hybrid composite comprised of silicon nanoparticles embedded in micron-sized amorphous carbon balls derived from corn starch that is capsuled by thin graphitic carbon layer. Such a dual carbon matrix tightly surrounds the silicon nanoparticles that provides high electronic conductivity and significantly decreases the absolute stress/strain of the material during multiple lithiation-delithiation processes. The Si-C hybrid composite anode demonstrates a high capacity of 1800 mAh g(-1), outstanding cycling stability with capacity retention of 80% over 500 cycles, and fast charge-discharge capability of 12 min. Moreover, the Si-C composite anode exhibits good acceptability in practical LIBs assembled with commercial Li[Ni0.6Co0.2Mn0.2]O-2 and Li[Ni0.80Co0.15Al0.05](2) cathodes.
Keywords: LITHIUM-ION; HIGH-ENERGY; POROUS CARBON; STORAGE; NANOSPHERES; ELECTRODES; CELLULOSE; CAPACITY; BIOMASS; SPHERES